Bees of the Colletes clypearis-group (Hymenoptera: Apoidea: Colletidae) from China with descriptions of seven new species - Niu, Ze-Qing; Zhu, Chao-Dong; Kuhlmann, Michael (Zootaxa, 2013)
Twenty-three known species of the Colletes clypearis speices group from China are treated in this paper. C. cinerascens Morawitz 1893, C. clypearis Morawitz 1876, C. floralis Eversmann 1852, C. impunctatus Nylander 1852, Colletes paratibeticus Kuhlmann 2002 and Colletes sodalis (Cameron 1897) are newly recorded from China. C. harrerioides sp. n., C. heilongtenensis sp. n., C. hirsutus sp. n., C. inspersus sp. n., C. xizangensis sp. n., C. xuezhongi sp. n. and C. yanruae sp. n. are described and illustrated as new species. Checklist of the known species from China in Colletes clypearis-group with distribution, floral records, and an illustrated key to all known males and females from China are provided. The type specimens of the new species are deposited in the Insect Collection of Institute of Zoology, Chinese Academy of Sciences, Beijing, China.